Psychological View on the Nature of Comical: the Attempt to Construct an Explanatory Conception - Zhovtianska, Valeria (Psychological Prospects Journal, 2019)
The article proposes the psychological conception that explains the essence of such phenomena as comical. According to this concept, comical occurs when an individual suddenly realizes the difference between his mental representation of an object and an object itself, and provided that before this difference is not reflexed by the individual. In the absence of such reflection, the separation of an image of the object from the object itself for the individual appears to be an ontologically impossible operation, therefore, from the subjective point of view, the essence of the comical is paradoxical. The proposed conception of comical is based on the theory that explains the patterns of mental representations’ forming. This theory implies that mental representations are formed in two stages. At the first stage intuitive, based on associations hypotheses about the quality of an object are created. At the second stage reflection and analytical testing of previous hypotheses are carried out. At the same time, such reflection and verification may not be performed or performed in a non-exhaustive manner. In this case mental representations remain not only unverified, but also not problematized, which leads to a subjective merging of the image of the object and the object itself. In this case mental representations constitute the potential basis for the appearance of comical. The article analyzes some conditions that lead to the separating in the mind of an individual a subjective representation about an object from the object itself. First of all we are talking about techniques that are used in humor. An analysis of these techniques allows to demonstrate the mechanisms that lead to the appearance of comical, and to illustrate psychological reality behind them.
Keywords: comical; humor; mental representation; reflection